Phase I clinical trial of KML001 monotherapy in patients with advanced solid tumors - Kim, Seokuee; Kim, Sujong; Park, Young Suk; Park, Joon Oh; Lim, Ho Yeong; Ahn, Jin Seok; Lee, Jeeyun; Sun, Jong Mu; Kang, Won Ki; Han, RaeO; Kim, Jungryul; Ahn, Myung-Ju (Expert opinion on investigational drugs, 2020)
We evaluated the tolerability, pharmacokinetics (PK) and preliminary efficacy of KML001, an oral trivalent arsenical, as a monotherapy in patients with advanced solid tumors. With a standard 3 + 3 design for dose-escalation stage, the planned dose levels of KML001 were 5, 7.5, 10, 12.5, and 15 mg/day for 28 days. Once the maximum tolerated dose was determined, 22 subjects were additionally enrolled for dose-expansion stage. PK analysis was performed in the 5, 10, and 15 mg/day cohort at the dose-escalation stage and also at the dose-expansion stage. Moreover, response was assessed using the standard RECIST 1.1. A total of 45 Korean subjects were enrolled. No DLT was reported at the dose-escalation stage. Three DLTs, two cases of prolonged QTc interval and one of neutropenia, were reported in the 12.5 mg/day cohort at the dose-expansion stage. Higher total daily doses up to 12.5 mg/day of KML001 resulted in higher trough plasma concentrations. Among the 18 subjects who completed 2 cycles of therapy, 15 had progressive disease and 3 had stable disease. Doses equal to or greater than 10 mg/day KML001 alone were tolerable and produced plasma concentrations higher than biologically relevant targets.